Effect of Health Education Using the Questions and Answers Module on Knowledge about Breastfeeding - Meilanda, Vella; Yanuarti, Riska; Wati, Nopia; Afriyanto; Pratiwi, Bintang Agustina (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Lack of knowledge about breastfeeding is often a major barrier for mothers to provide exclusive breastfeeding for the first six months of a baby's life, This is recommended as the optimal standard to support infant growth and health. This study aimed to evaluate the effectiveness of health education using the Questions and Answers module in improving knowledge about breastfeeding. Specifically, it sought to assess the extent to which this educational approach enhances participants' understanding of breastfeeding benefits, techniques, and common challenges. The study aimed to determine whether the interactive nature of the module leads to better knowledge retention compared to traditional educational methods. Subjects and Method: This was a quasi-experimental design involving 30 third trimester pregnant women who were divided into an intervention group and a control group. The intervention group received education based on question-and-answer modules, while the control group relied on standard Maternal and Child Health (MCH) books. The dependent variable included knowledge about breastfeeding. The independent variable was health education using the Questions and Answers module, as it represented the intervention aimed at improving participants' breastfeeding knowledge. The data were then collected by questionnaire. The mean difference of knowledge before and after question-and-answer modules was tested by independent t-test. Results: Knowledge scores about breastfeeding were higher in the intervention group (Mean= 19.60; SD= 2.13) than in the control group (Mean= 16.27; SD= 2.15), but this result was not statistically significant (p= 0.253). Conclusion: There was an increase in knowledge scores about breastfeeding after the Questions & Answers module was given, but the results were not statistically significant. There is a need to develop more interactive education programs to support mothers in providing exclusive breastfeeding, especially in areas with low levels of knowledge.